Analysis of the Pseudouridimycin Biosynthetic Pathway Provides Insights into the Formation of C-nucleoside Antibiotics. Issue 5 (17th May 2018) - Sosio, Margherita; Gaspari, Eleonora; Iorio, Marianna; Pessina, Silvia; Medema, Marnix H.; Bernasconi, Alice; Simone, Matteo; Maffioli, Sonia I.; Ebright, Richard H.; Donadio, Stefano
Summary: Pseudouridimycin (PUM) is a selective nucleoside-analog inhibitor of bacterial RNA polymerase with activity against Gram-positive and Gram-negative bacteria. PUM, produced by Streptomyces sp. ID38640, consists of a formamidinylated, N -hydroxylated Gly-Gln dipeptide conjugated to 5′-aminopseudouridine. We report the characterization of the PUM gene cluster. Bioinformatic analysis and mutational knockouts of pum genes with analysis of accumulated intermediates, define the PUM biosynthetic pathway. The work provides the first biosynthetic pathway of a C -nucleoside antibiotic and reveals three unexpected features: production of free pseudouridine by the dedicated pseudouridine synthase, PumJ; nucleoside activation by specialized oxidoreductases and aminotransferases; and peptide-bond formation by amide ligases. A central role in the PUM biosynthetic pathway is played by the PumJ, which represents a divergent branch within the TruD family of pseudouridine synthases. PumJ-like sequences are associated with diverse gene clusters likely to govern the biosynthesis of different classes of C -nucleoside antibiotics. Graphical Abstract: Highlights: Pseudouridimycin as a C -nucleoside antibiotic inhibiting bacterial RNA polymerase First biosynthetic pathway for a C -nucleoside antibiotic elucidated Free pseudouridine as a pathway intermediate Dedicated pseudouridine synthase, oxidoreductases, aminotransferases, amide ligases Abstract : Sosio et al. describe the biosynthetic pathway for the C -nucleoside antibiotic pseudouridimycin. Biosynthesis proceeds through formation of pseudouridine by the pseudouridine synthase PumJ, with specialized oxidoreductase, aminotransferase, and amide ligases leading to the final compound. Microbial genomes harbor diverse gene clusters encoding PumJ-related sequences.